Improved radiosynthesis and preliminary in vivo evaluation of a 18F-labeled glycopeptide–peptoid hybrid for PET imaging of neurotensin receptor 2. Issue 14 (15th July 2015) - Maschauer, Simone; Greff, Cornelia; Einsiedel, Jürgen; Ott, Julian; Tripal, Philipp; Hübner, Harald; Gmeiner, Peter; Prante, Olaf
Graphical abstract: Abstract: The neurotensin receptor 2 (NTS2) is an attractive target for cancer imaging, as it is overexpressed in a variety of tumor types including prostate, pancreas and breast carcinoma. The aim of this study was the development of the first NTS2 subtype selective 18 F-labeled radioligand for imaging NTS2 expression in vivo by positron emission tomography (PET). The radiosynthesis of glycopeptoid 18 F-4 was realized by copper(I)-catalyzed azide–alkyne cycloaddition (CuAAC), applying the prosthetic group 6-deoxy-6-[ 18 F]fluoroglucosyl azide for 18 F-fluoroglycosylation of the alkyne-terminated NT(8–13) analog Pra- N -Me-Arg-Arg-Pro- N -homo-Tyr-Ile-Leu-OH. The binding affinity of the peptide–peptoid4 for NTS2 was 7 nM with excellent subtype selectivity over NTS1 (260-fold). In vitro autoradiography studies of rat brain slices confirmed the high selectivity of 18 F-4 for NTS2. Biodistribution experiments using HT29 and PC3 tumor-bearing nude mice revealed high renal and only moderate tumor uptake, while PET imaging experiments revealed specific binding of 18 F-4 in NTS2-positive tumors. As 18 F-4 displayed high stability in vitro but fast degradation in vivo, future work will focus on the development of metabolically more stable NT(8–13) analogs.